2017
DOI: 10.2485/jhtb.26.257
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Evaluation of Bone Regeneration using Titanium Mesh Prepared by Selective Laser Melting Technique

Abstract: Various biochemical researches have been conducted for bone defects in the head, neck and maxillofacial region. Guided Bone Regeneration (GBR), which does not require any graft material, has focused on. However, GBR has been considered to be diffi cult to be used for critical-sized bone defects. In recent years, it has been made possible to make threedimensional (3D) structures by additive manufacturing, which titanium (Ti) powders are successively melted and solidifi ed (Selective Laser Melting technique; SLM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Thus, we previously evaluated the osteogenic activity in a study in which a rat calvarial bone defect was covered with the Ti mesh subjected to the MAH treatment, as well as other surface treatments. The results showed that the MAH-treated Ti mesh exhibited the highest bone formation in the bone defect area from an early stage, demonstrating the effectiveness of the MAH treatment on the Ti mesh [ 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we previously evaluated the osteogenic activity in a study in which a rat calvarial bone defect was covered with the Ti mesh subjected to the MAH treatment, as well as other surface treatments. The results showed that the MAH-treated Ti mesh exhibited the highest bone formation in the bone defect area from an early stage, demonstrating the effectiveness of the MAH treatment on the Ti mesh [ 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A surface roughness was produced on the Ti metal sample by the acid treatment, and this remained unchanged up to 600 ā€¢ C, but the sample surface roughness decreased above 700 ā€¢ C. Yamaguchi dipped mixed-acid and heat-treated Ti into simulated body fluid and then assessed its effect on bone formation [18]. In addition, Yamamoto et al [19,20] created a small bone defect in rat calvarial bones and implanted Ti mesh that had been subjected to various surface treatments into the defect. They found significantly greater bone formation with Ti specimens that had been subjected to mixed acid and heat treatment.…”
Section: Discussionmentioning
confidence: 99%
“… 23 The fact that Ti mesh prepared by SLM possesses osteogenic capacity is not inconsistent with our previous report. 24 …”
Section: Discussionmentioning
confidence: 99%